Evaluation of Procalcitonin and CRP in Diagnosing Acute Pelvic Inflammatory Disease - Iram Shahzadi, Farina Hayat, Ambreen Nasir, Nazia Muneer, Sidra Afzal, Sehrish Sabir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Acute pelvic inflammatory disease (PID) is a common gynecological emergency resulting frominfection and inflammation of the upper genital tract. Early diagnosis is essential to preventcomplications such as infertility, ectopic pregnancy